Sexual and reproductive health in adolescents of a doctor's office - Julia Tamara Alvarez Cortés; Lucila Engracia Revé Sigler; Ismael Leblanch Hernández; Minelia Torres Alvarado; Diana Esperanza Monet Alvarez (Centro Provincial de Información de Ciencias Médicas, 2017)
A descriptive and cross-sectional study of 54 adolescents with active sexual life, belonging to the doctor's office No. 15 of "Ramón López Peña" Polyclinic  was carried out in Santiago de Cuba, from March, 2016 to the same month in 2017, aimed at describing the characteristics of their sexual and reproductive health. Some variables were studied, such as age of beginningsexual relationships, use of protection methods, sexual satisfaction, history of sexually transmitted infections and number of pregnancies, childbirths, abortions and children. The existence of inadequate behaviors that affected these adolescents health sphere was proven. The early beginning of the unprotected sexual relationships, frequent change of sexual partner, high frequency of pregnancies, abortions, childbirths and sexually transmitted infections, were negative elements that demonstrated the existence of a low perception of the risks to which they were exposed.